Why study a Greek vase-painter?ña response to Whitley's 'Beazley as theorist' - Oakley, John H.
John Oakley defends the legacy of Beazley in response to James Whitley's recent analysis of Beazley and his followers (ANTIQUITY 72: 40Ð47). The debate demonstrates how influential some past figures of archaeological methodology still are, and how diverse are the approaches of modern scholars in interpreting and using their legacy.